Epidemiology in pure stands and varietal mixtures - Trutmann, P. (Centro Internacional de Agricultura Tropical (CIAT), Bean Programme for Central America, 1987)
A review is presented on disease development in bean var. mixtures and in pure stands, the effect on diseases of adding resistance components to susceptible mixtures, and the potential on nongenetic methods to control diseases in mixtures. Four mechanisms seem to reduce disease incidence in var. mixtures: the decrease in spatial density of susceptible plants, the barrier provided by resistant plants, the replacement of susceptible plants with resistant components, and induced resistance. (CIAT)